Activation of AMPK/SIRT1/FOXO3a signaling by BMS-477118 (saxagliptin) mitigates chronic colitis in rats: uncovering new anti-inflammatory and antifibrotic roles - Elmorsy, Elsayed A.; Youssef, Mahmoud E.; Abdel-Hamed, Mohamed R.; Amer, Maha M.; Elghandour, Sahar R.; Alkhamiss, Abdullah S.; Mohamed, Nahla B.; Khodeir, Mostafa M.; Elsisi, Hossam A.; Alsaeed, Thamir Saad; Kamal, Manal M.; Ellethy, Abousree T.; et al. (Frontiers in Pharmacology, 2024)
Ulcerative colitis (UC) is a debilitating chronic disease marked by persistent inflammation and intestinal fibrosis. Despite the availability of various treatments, many patients fail to achieve longterm remission, underscoring a significant unmet therapeutic need. BMS-477118, a reversible inhibitor of dipeptidyl peptidase 4 (DPP4), has demonstrated anti-inflammatory properties in preclinical and clinical studies with minimal adverse effects compared to other antidiabetic agents. However, the potential benefits of BMS-477118 in chronic UC have not yet been explored. In this study, we aimed to investigate the effects of BMS-477118 in rats subjected to chronic dextran sodium sulfate (DSS) administration. Our findings indicate that BMS-477118 activates the interconnected positive feedback loop involving AMPK, SIRT1, and FOXO3a, improving histological appearance in injured rat colons.BMS-477118 also reduced fibrotic changes associated with the chronic nature of the animal model, alleviated macroscopic damage and disease severity, and improved the colon weight-to-length ratio.Additionally, BMS-477118 prevented DSS-induced weight loss and enhanced tight junction proteins.These effects, in conjunction with reduced oxidative stress and its potential anti-inflammatory, antiapoptotic, and autophagy-inducing properties, fostered prolonged survival in rats with chronic UC.To conclude, BMS-477118 has the potential to activate the AMPK/SIRT1/FOXO3a signaling pathway in inflamed colons. These results suggest that the AMPK/SIRT1/FOXO3a pathway could be a new therapeutic target for UC. Further research is mandatory to explore the therapeutic possibilities of this pathway. Additionally, continued studies on the therapeutic potential of BMS-477118 and other DPP4 inhibitors are promising for creating new treatments for various conditions, including UC in diabetic patients.